2014
DOI: 10.1159/000364808
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Results and Higher-Order Aberrations after 1.4-mm Biaxial Cataract Surgery and Implantation of a New Aspheric Intraocular Lens

Abstract: The aspheric microincision IOL was safely implanted through a 1.4-mm incision and showed similarly good postoperative outcome in comparison to 1.8- and 2.2-mm coaxial phacoemulsification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
1
8
3
Order By: Relevance
“…Our study showed satisfying repeatability using the A-scan: the TRT value was 14.0345 μm, and the ICC value was 0.9797. Bao et al [30] assessed the repeatability of CCT with the A-scan. They found that the TRT value was 7.65 μm, and the ICC value was 0.994.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed satisfying repeatability using the A-scan: the TRT value was 14.0345 μm, and the ICC value was 0.9797. Bao et al [30] assessed the repeatability of CCT with the A-scan. They found that the TRT value was 7.65 μm, and the ICC value was 0.994.…”
Section: Discussionmentioning
confidence: 99%
“…It was treated with contact lens, and in day 4 the wound was stable without need for additional treatment. Other authors report anterior chamber instability during the surgery [ 5 ]. In our series of patients, where the Stellaris Phaco System with forced infusion was used, we did not observe above-mentioned problem.…”
Section: Discussionmentioning
confidence: 99%
“…B-MICS resulted from the interplay of several factors including microcorneal incisions, bimanuality, improved use of fluids, rapidly progressing instrumentation, and adequate use of low-energy ultrasound phacoemulsificators [ 2 ], including development of new sleeveless tip [ 3 , 4 ]. Advantages for this procedure are lower surgically induced astigmatism (SIA), less postoperative higher-order corneal aberrations (HOA) and lower endothelial cell loss [ 5 7 ]. Furthermore, it seems reasonable to conclude that smaller incision size has lower impact on corneal biomechanics, shortens recovery time and reduces number of endophthalmitis, although until now there is no clear evidence to support these hypotheses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a recent study [ 6 ], there are new aspheric intraocular lenses that are small enough to fit through a 1.4 mm incision, which saves the trouble of having an extra step for the IOL implant. Since the trend in cataract surgery has been to minimize the corneal incision, the 1.4 mm incision of B-MICS may have advantages in refractive surgery [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%